2021
DOI: 10.3390/vaccines9101152
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of COVID-19 Vaccine Acceptance, Hesitancy and Refusal among Employees of a Safety Net California County Health System with an Early and Aggressive Vaccination Program: Results from a Cross-Sectional Survey

Abstract: Since health professionals provide frontline care to COVID-19 patients, information on vaccine acceptance among healthcare workers is needed. We developed and implemented an anonymous internet-based cross-sectional survey with direct solicitation among employees of a safety net health system. Items queried demographic and health-related characteristics, experience with and knowledge of COVID-19, and determinants of decisions to vaccinate. COVID-19 vaccine acceptance groups (acceptors, hesitant, refusers) were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
50
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 47 publications
(85 reference statements)
7
50
0
1
Order By: Relevance
“…For example, the majority of respondents endorsed the statement that immunity from “natural” exposure to disease lasts longer than vaccination, suggesting that information about the stability of COVID-19 vaccine immunity should be disseminated to frontline nurses and frequently updated as these data emerge. This is consistent with survey data from the Riverside University Health System in California finding vaccine-hesitant HCWs were the least knowledgeable about COVID-19 disease [25] and from HCWs in five European countries showing that high self-perceived knowledge about COVID-19 vaccines was correlated with increased COVID-19 vaccine intent [26] . Additionally, directly addressing the unique circumstances under which COVID-19 vaccine development was expedited but still approved for emergency use through the standard rigorous requirements could also help assuage nurses’ safety concerns, especially since the oft-cited fears about the COVID-19 vaccines’ rapid development and potential side effects, including possible effects on fertility, continue to persist [27] , [28] .…”
Section: Discussionsupporting
confidence: 87%
“…For example, the majority of respondents endorsed the statement that immunity from “natural” exposure to disease lasts longer than vaccination, suggesting that information about the stability of COVID-19 vaccine immunity should be disseminated to frontline nurses and frequently updated as these data emerge. This is consistent with survey data from the Riverside University Health System in California finding vaccine-hesitant HCWs were the least knowledgeable about COVID-19 disease [25] and from HCWs in five European countries showing that high self-perceived knowledge about COVID-19 vaccines was correlated with increased COVID-19 vaccine intent [26] . Additionally, directly addressing the unique circumstances under which COVID-19 vaccine development was expedited but still approved for emergency use through the standard rigorous requirements could also help assuage nurses’ safety concerns, especially since the oft-cited fears about the COVID-19 vaccines’ rapid development and potential side effects, including possible effects on fertility, continue to persist [27] , [28] .…”
Section: Discussionsupporting
confidence: 87%
“…These results reveal that physicians were more prone to VH, diverging from previous literature. 17 , 41 Studies before vaccines’ approval showed that nurses tended to be significantly more reluctant when compared to physicians. 8 , 12 , 42 These differences may be related to the fact that these studies report to a period before the implementation of widespread vaccination strategies, as nurses are currently the main professional group that administers the vaccines to the population.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted regarding the hesitancy of health professionals towards COVID‐19 vaccination both during the months of the pandemic in which there were no vaccines approved and post‐vaccines approval. 8 , 12 , 13 , 14 , 15 , 16 , 17 The reason for choosing this at‐risk population was related to their role in combatting the COVID‐19 pandemic and their priority in receiving the COVID‐19 vaccine in Portugal, their risk for contracting the disease and their close contact with COVID‐19 patients in a professional context. Furthermore, studying vaccine hesitancy in health professionals is important not only to understand what drives their hesitancy but also because they can highly influence the attitudes and behaviours of their patients towards vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…The contributing factors for COVID-19 vaccine hesitancy can vary. Social media organization [4] vaccine characteristics [5] political affiliations [6], education level [7], employment, risk of infection [8]distrust of the COVID-19 vaccine [9], and general vaccine avoidance [10]…”
Section: Introductionmentioning
confidence: 99%
“…The contributing factors for COVID-19 vaccine hesitancy can vary. Social media organization [4] vaccine characteristics [5] political affiliations [6], education level[7], employment, risk of infection [8]distrust of the COVID-19 vaccine [9], and general vaccine avoidance [10] have been associated with COVID-19 vaccine hesitancy. Past studies looking into COVID-19 vaccine hesitancy have used a large-n cross-country regression framework, survey with choice-based conjoint analysis, and regression analyses have been used to analyze data in previous studies.…”
Section: Introductionmentioning
confidence: 99%